Urban Planning for Healthy European Cities - D'Onofrio, Rosalba (SpringerBriefs in Geography,, 2018)
This book investigates different aspects of the relationship between "healthy cities" and "urban planning", examining various best practices in Europe. It uses the above as a starting point and investigates different aspects of healthy cities, examining various best practices in Europe. Capitalizing on ongoing trials, the chapters identify the policies that underlie plans and projects that have caused positive changes in local communities in terms of the quality of life and safety of inhabitants. From these best practices, the book deduces criteria and guidelines for planning healthy and safe cities.